2022
DOI: 10.1186/s12905-022-01816-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal employment on exclusive breastfeeding practice among mothers of infants 6–12 months old in Wolkite town, Ethiopia: a comparative cross-sectional study

Abstract: Introduction Exclusive breastfeeding (EBF) means providing only breast milk for infants for up to six months without the addition of solid or liquid matter. Even though EBF had great benefits for infants and mothers, the rate of EBF is so limited below the global target. In Ethiopia, the overall EBF practice is 59%. This low EBF practice had a great unexplained variation among employed and unemployed mothers. Therefore, this study aimed to compare EBF practice and associated factors among emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The study shows a high proportion of housewives 80.9% practicing EBF than employed mothers 67.8%. The findings are almost consistent with the previous study's reported EBF of 73% for unemployed mothers and 54.8% for employed mothers [ 9 ]. Furthermore, a high proportion of EBF was observed among non-working women (75.5%) compared to working women 26.5% [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study shows a high proportion of housewives 80.9% practicing EBF than employed mothers 67.8%. The findings are almost consistent with the previous study's reported EBF of 73% for unemployed mothers and 54.8% for employed mothers [ 9 ]. Furthermore, a high proportion of EBF was observed among non-working women (75.5%) compared to working women 26.5% [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has been recommended by Jiawen Chen that if the workplace is near home, work schedules are flexible and workplace policies support the breastfeeding environment, the rate of EBF is likely to increase [ 8 ]. Several studies have been previously carried out to compare EBF for employed and unemployed mothers; for instance, the EBF practice in Ethiopia was 54.8% for employed mothers and 73% for unemployed [ 9 ], while in Ghana, the EBF was 16% for employed and 84% for unemployed [ 10 ], and in Somali, the EBF was 24.8% for employed and 82.9% for unemployed mothers [ 11 ]. Studies indicate that employed mothers have poor EBF practices compared to unemployed.…”
Section: Introductionmentioning
confidence: 99%
“…Provide childcare [ 43 ], onsite childcare [ 112 , 117 , 119 ] where mothers can breastfeed [ 105 ] or nearby childcare [ 110 , 134 , 136 ]…”
Section: Resultsmentioning
confidence: 99%
“…Menyusui secara eksklusif merupakan aktivitas pemberian Air Susu Ibu (ASI) tanpa asupan tambahan pada bayi umur 0-6 bulan (Zewdie et al, 2022). Peran terbesar menyusui ada pada ibu, namun akan lebih mudah menjalankannya bila seluruh pihak ikut berperan.…”
Section: Pendahuluanunclassified